The impact of nutrition and statins on cardiovascular diseases - Zabetakis, Ioannis; Lordan, Ronan; Tsoupras, Alexandros (Academic Press, 2019)
'The Impact of Nutrition and Statins on Cardiovascular Diseases' presents a summary of the background information and published research on the role of food in inhibiting the development of cardiovascular diseases. Written from a food science, food chemistry, and food biochemistry perspective, the book provides insights on the origin of cardiovascular diseases, an analysis of statin therapy, their side effects, and the role of dietary intervention as an alternative solution to preventing cardiovascular diseases. It focuses on the efficacy of nutrition and statins to address inflammation and inhibit the onset of disease, while also providing nutrition information and suggested dietary interventions. Key Features: Includes a bioscience approach that focuses on inflammation and revisits the lipid hypothesis; Presents the view that nutritional interventions have considerable value, not only for reducing cardiovascular risk for CVDs patients, but also acting as the best precaution for otherwise healthy people; Advocates that nutritional habits that are formed at a young age are the best way to tackle the global epidemic that is CVDs. --